IMPLEMENTASI FUZZY LOGIC CONTROL DENGAN METODE MAMDANI UNTUK PENGONTROLAN TEMPERATUR HEATING PAD PADA WEARPACK - Suswanto, Althaf Juldha; Rusli, Moch.; Sari, Sapriesty Nainy (Jurnal Mahasiswa TEUB, 2024)
The lack of awareness of workers in the importance of occupational safety and health (K3) makes the high risk of work accidents in Indonesia. Especially in the highlands, workers have a risk of developing hypothermia due to extreme temperatures. The purpose of this research in designing a wearpack that can provide external heat to the user's body using a heating pad that can control the temperature automatically using fuzzy logic control mamdani method which will be processed using ESP-32 Dev Kit as a microcontroller. Based on the tests carried out, it can be concluded that the design of the device made is in accordance with the expected specifications where the device is able to change the temperature on the heating pad based on the output of the fuzzy logic control calculation in the form of PWM. In testing of a temperature input of 27°C and a bpm of 61, the PWM output on the L289N driver is obtained with a time constant of 1,63 seconds and a steady state gain of 5,82 %/V with an output voltage of 2.54 volts. It can be concluded that the tool is able to issue PWM output in accordance with the input of the two sensors after going through fuzzy logic calculations. Keywords: ESP-32 Dev Kit, PWM, Heating Pad, Fuzzy Logic, Mamdani